The influence of Pfannenstiel and midline incisions to the wound condition on the third day post gynecologic surgery - Nita Tri Kurniati Sulchan Sofoewan Ibnu Pranoto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2012)
Many factors should be considered by a surgeon to choose an abdominal incision, such as incision extensibility, speed of operation, presence or absence of adhisions, hemostasis problems, possibility of postoperative complications such as infections, hernia or dehiscence, and wound healing. Midline or linea mediana incision makes the field operation seem wider, therefore the operations can be performed more uickly. Meanwhile, transverse incision such as Pfannenstielincision is gaining popularity with the less incidence of infection, hernia, and wound dehiscence because this technique follows Langer’s lines resulting in reduced traction at the skin edges and making better wound closure and approximation. This study aimed to evaluate the influence ofPfannenstiel and midline incisions to the wound condition on the third day post gynecologic surgery. This was an observational study using a prospective cohort study design. The subjects were patients with the indications for gynecologic surgery in Dr. Sardjito General HospitalYogyakarta and affiliated hospitals who fulfilled the inclusion and exclusion criteria. Sixty subjects were divided into two groups i.e. 30 subjects who underwent Pfannenstiel incision as treatment group and 30 subjects who underwent linea mediana incision as control group. The characteristicsof subjects of both group were not significantly different. No significant difference of the wound condition on the third day after surgery between subjects who underwent Pfannenstiel and linea mediana incisions was observed in this study (p=0.212). The risk of the wound beingnot dried yet on the third day after sugery on subjects who underwent linea mediana incision technique was 2.5 times higher compared to subjects who underwent Pfannenstiel incision technique. However, it was not statistically different (p= 0.212; RR= 2.5; 95%CI= 0.525-11.894). In conclusion, there is no significantly different effect of Pfannenstiel and linea mediana incisions to the wound condition on the third day post gynecologic surgery.Keywords: Pfannenstiel incision - midline incision - wound healing - gynecologic surgery -complication